Flexural strength of Lightweight geopolymer concrete using sisal fibres. (2021) - Kavipriya, S.; Deepanraj, C.G.; Dinesh, S.; Prakhash, N.; Lingeshwaran, N.; Ramkumar, S.
Abstract: Lightweight concrete is usually chosen for structural purpose where its use will lead to a lower overall cost of a structure than normal weight concrete by reducing its dead weight. This weight will make it an uneconomical structural material. Attempts have been made in the past to reduce the self-weight of concrete to increase the efficiency of concrete as a structural material. In this research, bamboo sticks are used in the form of coarse aggregate at different proportions to reduce the self-weight of concrete. Also, naturally available fibre named sisal fibre is into the reinforcement to study its properties. The influence of sisal fibres and bamboo sticks on the strength of light weight geopolymer concrete is taken as the main objective of this experimental study. In recent years, a great deal of interest has been created worldwide on the potential applications of light weight concrete and utilization of natural fibres reinforced cement-based composites. In this work, it is also aimed to investigate the strength properties of concrete by casting light weight geopolymer concrete by replacing bamboo aggregates with 10%, 20% and 30% of coarse aggregate. Also, Sisal fibres are added at different proportions as 0.25%, 0.5%, 0.75% and 1.0% by volume of concrete respectively. Evaluation of flexural bending strength for M25 geopolymer concrete specimens was done. Totally 9 number of 500×100×100 mm flexural members are cast and tested under M25 grade of concrete. The 12 M NaOH, ratio of NaOH:Na2 SiO3 as 2.5 and ratio of flyash to alkaline activator solution as 0.6 are considered as various parameters for designing the mix of geopolymer concrete. Ambient curing condition is applied for evaluating strength properties. The flexure strength was tested with replacement of coarse aggregate with bamboo sticks and by adding different percentage of sisal fibres. The test results indicated that the sisal fibres were effective in improving the strength of concrete.